A Starting Point for Practitioner Inquiry: A Review of The Reflective Educator’s Guide to Classroom Research - Christopher B. Crowley (Networks: An Online Journal for Teacher Research, 2009)
In first part of this essay, I will introduce my discussion of The Reflective Educator’s Guide to Classroom Research by describing my general impressions of the book. Next, I will provide a brief overview of the book and its main ideas. Finally, I will discuss some critical considerations that I believe are worth considering when discussing practitioner inquiry.